The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016 European Control Conference (ECC) 2016
DOI: 10.1109/ecc.2016.7810492
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative indoor positioning by exchange of bluetooth signals and state estimates between users

Abstract: This paper presents a Bayesian indoor positioning system for smartphones based on the strengths of WiFi and Bluetooth signals. A framework for improving the performance of existing positioning methods with the help information sharing between users is proposed and evaluated. Bluetooth signals are sent between users, and the signal strengths contain information about their relative distances, which is used to evaluate the probability distribution functions of their states. A particle filter is used for the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…A majority of research focuses on positioning scenarios in existing buildings, some of them re-using already existing infrastructure (i.e., signals of opportunity). Typical scenarios that are receiving a growing interest involve locating people within houses, offices [ 63 , 115 , 123 , 131 ], and universities [ 40 , 43 , 63 , 79 , 98 , 101 , 119 , 120 , 128 , 131 ], where the viability of installing complex infrastructure is low in terms of costs, unlike industrial or warehouse scenarios, which are capable of developing and deploying robust and costly infrastructures designed for positioning. As a result, our review indeed shows that infrastructure-less approaches are predominantly selected for CIPSs in research (see Figure 4 c), and that the majority of technologies used (see Figure 5 and Figure 6 ) are already present in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A majority of research focuses on positioning scenarios in existing buildings, some of them re-using already existing infrastructure (i.e., signals of opportunity). Typical scenarios that are receiving a growing interest involve locating people within houses, offices [ 63 , 115 , 123 , 131 ], and universities [ 40 , 43 , 63 , 79 , 98 , 101 , 119 , 120 , 128 , 131 ], where the viability of installing complex infrastructure is low in terms of costs, unlike industrial or warehouse scenarios, which are capable of developing and deploying robust and costly infrastructures designed for positioning. As a result, our review indeed shows that infrastructure-less approaches are predominantly selected for CIPSs in research (see Figure 4 c), and that the majority of technologies used (see Figure 5 and Figure 6 ) are already present in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The results provided in Section 4.3 showed that in 66 articles, positioning was done in two steps: each node or actor used an indoor positioning method (based on one or multiple positioning technologies) to get an initial estimation with only its collected data [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 63 , 77 , 79 , 80 , 81 , 83 , 84 , 86 , 87 , 89 , 91 , 92 , 93 , 94 , 97 , 98 , 100 , 101 , 102 , 103 , 104 , 106 , 107 , 108 , 109 , 110 , 111 , 113 , 114 , 116 , 117 , 118 , 119 , 120 , 123 , 124 , 125 , 127 , 128 , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karlsson et al [32] showed smartphone based Wi-Fi signal measurements exchange via Bluetooth connection between the users. They used Bluetooth signal strength difference between users to calculate relative distance, which is used to evaluate the probability distribution functions of their states.…”
Section: Related Workmentioning
confidence: 99%